2015
DOI: 10.1111/aor.12508
|View full text |Cite
|
Sign up to set email alerts
|

Displacement or Force Control Knee Simulators? Variations in Kinematics and in Wear

Abstract: The problems associated with prosthetic failure and revision surgery still constitute the main clinical problem of prosthetic surgery. The objective of wear evaluation is to determine the wear rate and its dependence on the test conditions. To obtain realistic results, a wear test can be performed to reproduce in vivo working conditions and compare the wear characteristics of various total knee prostheses designs. At the state of the art, two simulation concepts are available and defined in ISO 14243 standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Ideally, the preclinical endurance testing should reproduce on the artificial implants the in vivo conditions of load and motion experimented by the human joint in order to assess the wear of prosthetic components and give information about materials and design optimization for prosthetic implants. The research in this field has been going on for many years [3,4] and is still strongly active in order to further increase the service life of TKRs, as evidenced by the many studies [5,6,7]. At the state of the art, two simulation concepts for the knee joint are available and defined by the International Organization for Standardization (ISO) 14243-1/3 standards: the force control (FC) and the displacement control (DC) [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the preclinical endurance testing should reproduce on the artificial implants the in vivo conditions of load and motion experimented by the human joint in order to assess the wear of prosthetic components and give information about materials and design optimization for prosthetic implants. The research in this field has been going on for many years [3,4] and is still strongly active in order to further increase the service life of TKRs, as evidenced by the many studies [5,6,7]. At the state of the art, two simulation concepts for the knee joint are available and defined by the International Organization for Standardization (ISO) 14243-1/3 standards: the force control (FC) and the displacement control (DC) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The level walking is the sole activity of daily living that is represented for testing. Recently, significant differences in the features of wear and surface finish between knee replacements subjected to in vitro simulation and implants obtained from explants have been noticed [7,10]. These discrepancies may be due to differences between the kinematic and dynamic profile impressed on the in vivo joint and the one defined by the ISO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on wearing of knee implants [ 24 25 ] failed to consider variations in the direction of AP and TR, which has been shown in this study to be a critical factor in determining knee kinematics and the level of wear on the tibial insert. Similarly, Schwenke T et al [ 24 ] reported marked differences in wear rates between displacement control and load control methods.…”
Section: Discussionmentioning
confidence: 79%
“…A number of studies [ 24 29 ] have investigated how varying the parameters outlined in ISO 14243 may impact the knee joint; differences in wear between load and displacement control [ 24 25 ], the effect of varying the amplitude of inputs for displacement control on wear [ 26 ], the effect of anterior-posterior and internal-external motion constraints on wear [ 27 ], the impact of different activities on the wear performance [ 28 ], comparison between electromechanically- and pneumatically-controlled knee simulators [ 29 ]. To the best of our knowledge, no previous studies considered the influence of altering the direction of AP and TR on wear rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, a displacement control simulation has the advantage of providing a consistent path, displacement, surface velocity, and phasing relative to the femoral flexion and axial load, resulting in a consistent force velocity. 57…”
Section: Discussionmentioning
confidence: 99%